Rhetorics of Opacity, Social Change, and Communal Cultivation: Case Studies of GLBTQ Christian Advocacy During the 1960s and Early 1970s - (:unkn) unknown (My University, 2018)
This dissertation probes questions about community and advocacy, analyzing four case studies involving GLBTQ Christian advocacy from the early 1960s to the early 1970s. Each case study involves the use of rhetoric to hide or downplay markers of the at-the-time stigmatized “homosexual” identity. The examined case studies are Bayard Rustin’s advocacy work with the Southern Christian Leadership Conference, the Council on Religion and the Homosexual, William Johnson’s ordination paper, and the 1973 Christian Reformed Church’s study report. To engage these texts, the dissertation develops theories about and methods for examining rhetorics of opacity—silence, hidden appeals, discourse that obscures, rhetorics of minimalization, and distraction. I argue that rhetorics of opacity can constitute powerful, yet complex and precarious, appeals that enable political and shared action, cultivate and constitute community, and foster social change and inclusion. This conceptualization offers rhetorical scholarship a fuller appreciation of the ways in which opacity and self-silencing comprise critical rhetorical strategies in campaigns for social change. Especially in treacherous, oppressive, and deadly social contexts and environments, the utilization of opaque rhetorics might constitute a viable strategy for advocates seeking transformation and communal empowerment while minimizing the risk that harm will befall on them for trying to foster change.
Keywords: Advocacy; Community; GLBTQ Rhetoric; Opacity; Passing; Social Change